Feint of Heart Art Writings, 1982-2002 - Hickey, Dave 1940- (David Zwirner Books, 2024)
"From the legendary and iconoclastic critic Dave Hickey, a collection of twenty of his most emblematic essays on art. The late Dave Hickey was a singular voice on art, music, democracy, and culture. Known for his radical criticism, he united different worlds through a range of literary styles and techniques to ultimately explore what it means to be human. Complementing his iconic collections Air Guitar and The Invisible Dragon, Feint of Heart unites twenty of Hickey's characteristically astute essays on art from over twenty years, most of which were originally published in exhibition catalogues that are long out of print. The result is a volume that shows the writer at his most creative and incisive in an ever-relevant exploration of beauty and value. Compiled and with an introduction by the writer and critic Jarrett Earnest, this latest book is ideal for cult followers and new readers of Hickey, for artists and art critics, and for thinkers across all disciplines. Including essays on Terry Allen, Karen Carson, Sarah Charlesworth, Vija Celmins, Vernon Fisher, Robert Gober, Ann Hamilton, Luis Jiménez, Hung Lui, Josiah McElheny, Elizabeth Peyton, Lari Pittman, David Reed, Bridget Riley, Norman Rockwell, Ed Ruscha, Steve Schapiro, Richard Serra, and Andy Warhol, as well as Hickey's 2002 text "Buying the World," an incisive and ever-relevant exploration of beauty and value."
Includes bibliographical references and index
Keywords: Kunst; USA; Art; ART / General; Essays; Aufsatzsammlung